2008
DOI: 10.1074/jbc.m707957200
|View full text |Cite
|
Sign up to set email alerts
|

Access Denied: Snf1 Activation Loop Phosphorylation Is Controlled by Availability of the Phosphorylated Threonine 210 to the PP1 Phosphatase

Abstract: Phosphorylation of the Saccharomyces cerevisiae Snf1 kinase activation loop is determined by the integration of two reaction rates: the rate of phosphorylation by upstream kinases and the rate of dephosphorylation by Glc7. The activities of the Snf1-activating kinases do not appear to be glucose-regulated, since immune complex kinase assays with each of the three Snf1-activating kinases show similar levels of activity when prepared from cells grown in either high or low glucose. In contrast, the dephosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
136
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(144 citation statements)
references
References 46 publications
7
136
0
Order By: Relevance
“…Although the possibility of regulation of the activating kinases is not excluded, there is no evidence to support this idea; these kinases had similar activity when prepared from cells grown on high or low glucose (9), and expression of AMPK-activating kinases in yeast sufficed for glucoseregulated activation of SNF1 (10).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although the possibility of regulation of the activating kinases is not excluded, there is no evidence to support this idea; these kinases had similar activity when prepared from cells grown on high or low glucose (9), and expression of AMPK-activating kinases in yeast sufficed for glucoseregulated activation of SNF1 (10).…”
Section: Discussionmentioning
confidence: 93%
“…Phosphorylation of the activation-loop Thr of the catalytic subunit activates SNF1/AMPK. For SNF1, the protein kinases Sak1, Tos3, and Elm1 phosphorylate Thr-210 on the Snf1/α subunit in response to glucose limitation and other stresses (5)(6)(7)(8), but there is no evidence that these Snf1-activating kinases are regulated (9,10). Less is understood about the protein phosphatases that deactivate SNF1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In support of such a crucial role for the phosphatase in the regulation of Snf1 activity, it was recently reported that the dephosphorylation rate of Snf1 is more subject to glucose regulation than the phosphorylation rate (Rubenstein et al 2008). However, it also appears that the catalytic activity of the Glc7-Reg1 phosphatase itself is not controlled by glucose, but rather Snf1 itself, in such a way that the ability of the Snf1 activation loop to act as a substrate for Glc7-Reg1 is adapted to glucose availability (Rubenstein et al 2008).…”
Section: Structure and Regulation Of The Snf1 Kinasementioning
confidence: 98%
“…In yeast, the AS strategy has been useful in determining the function of many kinases including Cdc28 (10, 11), Ime2 (11), Cla4 (12), and Snf1 (13). Several discoveries using this approach have also been made in mammalian systems including a noncatalytic role for Zap70 in regulatory T-cells (14), and the dependence of transformed cells on aberrant oncogenic signaling by the EGFR kinase (15).…”
Section: Chemical Genetics | Irreversible Inhibitor | Sgk494mentioning
confidence: 99%